Sono-Photocatalytic Activity of Cloisite 30B/ZnO/Ag2O Nanocomposite for the Simultaneous Degradation of Crystal Violet and Methylene Blue Dyes in Aqueous Media - Rauf Foroutan; Seyed Jamaleddin Peighambardoust; Daria Camilla Boffito; Bahman Ramavandi (Nanomaterials, 2022)
A new nanocomposite based on Cloisite 30B clay modified with ZnO and Ag2O nanoparticles (Cloisite 30B/ZnO/Ag2O) was synthesized as an effective catalyst in the sono-photocatalytic process of crystal violet (CV) and methylene blue (MB) dyes simultaneously. The characteristics and catalytic activity of Cloisite 30B/ZnO/Ag2O nanocomposite were investigated under different conditions. The specific active surface for Cloisite 30B/ZnO/Ag2O nanocomposite was 18.29 m2/g. Additionally, the catalytic activity showed that Cloisite 30B/ZnO/Ag2O nanocomposite (CV: 99.21%, MB: 98.43%) compared to Cloisite 30B/Ag2O (CV: 85.38%, MB: 83.62%) and Ag2O (CV: 68.21%, MB: 66.41%) has more catalytic activity. The catalytic activity of Cloisite 30B/ZnO/Ag2O using the sono-photocatalytic process had the maximum efficiency (CV: 99.21%, MB: 98.43%) at pH 8, time of 50 min, amount of 40 mM H2O2, catalyst dose of 0.5 g/L, and the concentration of ‘CV + MB’ of 5 mg/L. The catalyst can be reused in the sono-photocatalytic process for up to six steps. According to the results, •OH and h+ were effective in the degradation of the desired dyes using the desired method. Data followed the pseudo-first-order kinetic model. The method used in this research is an efficient and promising method to remove dyes from wastewater.